STRUCTURAL TRANSFORMATION OF ECONOMY IN SPECIAL REGION OF YOGYAKARTA - Nur Feriyanto (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2015)
The first aim of this study was to determine the relationship between the growth rate of GRDP and the growth rate of sectors’ labor absorption in Special Region of Yogyakarta. The second objective was using the Esteban Marquillas’ Shift-Share analysis to prove whether there has been a structural transformation of the economy in Special Region of Yogyakarta during 2009-2014. The third aim was to determine the impact of economic sectors’ growth in Indonesia on the growth of aggregate GRDP in Special Region of Yogyakarta. Results of this study were: (1) There were three conditions used to observe the relationship between the growth rate of GRDP and the growth rate of labor absorption in Special Region of Yogyakarta namely anomalous, regressive, and progressive. (2) The use of Esteban Marquillas’ Shift-Share analysis showed that in the area of Special Region of Yogyakarta there had been a shift in the economic structure from the primary sector to the secondary and tertiary sectors. (3) The economic sectors’ growth in Indonesia could lead to the growth of aggregate GRDP in Special Region of Yogyakarta as much as 539.53 billion IDR. Suggestions offered by this research are as follows: (1) policy making by the government related to development has to pay attention to the relationship between economic growth and unemployment rate. (2) Government has to address the economic transformation from primary to tertiary sectors, especially for development planning; and (3) government needs to focus on economic development for the dominant sectors of economy in DIY province.